2017
DOI: 10.1038/onc.2017.321
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinase-1 promotes cell proliferation through YAP/TAZ activation in cancer

Abstract: Tissue inhibitor of metalloproteinase-1 (TIMP-1), a member of the TIMP family (TIMP-1 to 4), is highly expressed in various types of cancer and forms a complex with its receptor CD63 and Integrin β1. However, the precise oncogenic mechanism of TIMP-1 remains unclear. Yes-associated protein (YAP) and transcriptional co-activator with PDZ binding motif (TAZ) are transcription co-activators enhancing the transcription of specific genes related to cell proliferation. But the mechanism of aberrant YAP/TAZ activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…Upon ITGB1 activation, FAK auto-phosphorylates Tyr-397 and recruits the kinases SRC and PI3K (Ando et al, 2018;Toricelli et al, 2013). Because FAK is a central node in the ITGB1 signaling cascade, we hypothesized that FAK, and substrate kinases SRC and PI3K, impacted on hypermotility.…”
Section: Fak (Ptk2) Silencing Impedes DC Hypermotilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Upon ITGB1 activation, FAK auto-phosphorylates Tyr-397 and recruits the kinases SRC and PI3K (Ando et al, 2018;Toricelli et al, 2013). Because FAK is a central node in the ITGB1 signaling cascade, we hypothesized that FAK, and substrate kinases SRC and PI3K, impacted on hypermotility.…”
Section: Fak (Ptk2) Silencing Impedes DC Hypermotilitymentioning
confidence: 99%
“…Gene silencing of Timp-1 (shTIMP-1), Cd63 (shCD63) and Itgb1 (shITGB1) and Ab blockade of ITGB1 (Ha2/5 and HMβ1-1) inhibits hypermotility while recombinant mouse TIMP-1 (rmTIMP-1) rescues hypermotility of shTIMP-1-silenced T. gondii-infected DCs. (V) Activated ITGB1 induces FAK Tyr-397 auto-phosphorylation, which in turn activates SRC and PI3K signaling (Ando et al, 2018;Toricelli et al, 2013). FAK and SRC are phosphorylated shortly after challenge with T. gondii.…”
Section: Lentiviral Vector Production and In Vitro Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMP1 has been identified as an oncogenic MMP‐independent regulator of cell proliferation and apoptosis in various cell types . In an attempt to define the functional contribution of TIMP1 overexpression in gastric cancer, we have employed in vitro cell models to detect the effect of the TIMP1 inhibition on cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that Src can promote YAP/TAZ activity through multiple independent mechanisms ( Figure 2 ) [ 85 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 ]. Src and other Src family kinases (SFKs) can directly phosphorylate YAP [ 85 , 251 , 253 , 255 , 256 , 261 ] and TAZ [ 257 ] to promote their protein stability and activity.…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%